Pakistan People’s Party: A Historical Analysis of Ideological Debates within the Party (1967-1977) - Muhammad Qasim Sodhar; Sobia Jamil; Adeela Ghazanfar (ASIAN Journal of International Peace & Security (AJIPS), 2024)
The debate surrounding the political ideology of the Pakistan People’s Party (PPP), particularly under the leadership of its founder, Zulfiqar Ali Bhutto, continues to be a topic of contention. There exist varying perspectives on this matter. One school of thought asserts that Mr. Bhutto was a socialist who earnestly endeavored to implement socialist principles in Pakistan, albeit encountering obstacles that impeded his success. Conversely, another school of thought outright refutes this claim, positing that Bhutto was a populist leader who exploited socialist rhetoric for personal and party gains. In this paper, the foundational documents of the Pakistan People’s Party (PPP) – namely, the Foundation Documents and its initial election manifesto from 1970 – are examined to gauge the extent to which socialist ideology was embedded in the party records, and to delve into the PPP’s stance on socialism. Furthermore, the paper seeks to understand the factors contributing to the PPP’s popularity in Sindh as opposed to other leftist parties.